SEISMIC ATTRIBUTE ANALYSIS AND RESERVOIR CHARACTERIZATION OF ‘’GEORGE’’ FIELD, OFFSHORE NIGER DELTA, NIGERIA - M. T, Olowokere,; O, Abiola; J. S, Ojo (IJRDO-Journal of Applied Science, 2017)
Seismic Attribute Analysis and Reservoir Characterization of ‘George Field’ offshore NigerDelta was carried out with a view to determining the hydrocarbon potential of the area. The dataset used for the study includes three dimensional seismic data and a suite of geophysical welllogs from four wells A, B, C and D. In order to further confirm the presence of hydrocarbon inthe identified structures, attribute analysis was carried out. The energy and the amplitudeattribute extraction maps and the instantaneous frequency volume attributes maps for thereservoirs were generated. The trapping mechanism is a fault assisted closure. The amplitude,average energy and instantaneous frequency extraction maps revealed higher values around thestructural highs which coincide with the locations where producing wells A, B, C and D hadalready been drilled thereby validating earlier interpretations that led to their drilling.